GPS as a geodetic tool for geodynamics in northern Victoria Land, Antarctica - A. Capra; F. Mancini; M. Negusini (Antarctic Science, 2007)
The VLNDEF (Victoria Land Network for DEFormation control) project started in 1999 with the aim of detecting crustal deformation in Northern Victoria Land (Antarctica) over an area that had never been surveyed by a dense GPS network before. After a brief summary of the Italian geodetic activities carried out since 1991, the paper presents the results obtained from the processing of data collected from 1999 to 2003. In particular, processing strategies were dealt with, in order to produce horizontal and vertical displacement maps through GPS observations. Absolute motions in a global reference frame have been investigated using a double approach, which allowed us to make considerable progress in detecting movements and standardizing the data analysis. The analyses provide absolute horizontal velocities ranging between 17 mm yr(-1) and 8 mm yr(-1), with greater motions in the northernmost area. The subtraction of the rigid plate motion provides relative displacements, which may contribute to the understanding of neotectonics and geology, whereas the pattern of the vertical crustal motions detected, with average values of +1.3 mm yr(-1), is essential to detect the effect of Glacial Isostatic Adjustment (GIA) and other geophysical signals, and to redefine theory and numerical models used without any direct measurements.